American Community Colleges: The International Student’s Guide - Martirosyan, Nara M. (Journal of International Students, 2018)
As a former international student, I never thought of an American Community College as being a choice to start undergraduate education in the United States. This is also true for many prospective international students who explore study opportunities in the United States. American community colleges (also called 2-year colleges) offer diverse higher education opportunities with comparatively lower tuition costs. Moreover, unlike in many other foreign countries, American community colleges are often the best pathway to a bachelor’s degree through transfer agreements that exist between community colleges and 4-year institutions.